Level of Knowledge Sports Coaching Education Students Related to Scientific Journal Articles - Nurkadri Nurkadri; Novita Novita; Hendro Septiadi Sihombing; Ingrid Margaretha Sitorus; Mangasi Malatua (Universitas PGRI Palembang, 2023)
The development of the educational model in Indonesia is students as active scientists, in this case the students of Medan State University, one of whom is a student of the Sports Coaching Education Study Program, Faculty of Sports Science, whose one of his duties is Critical Journal Review. Based on the above, the researcher aims to find out how the students' understanding of the UNIMED FIK Sports Coaching Education Study Program is related to writing scientific articles that are journalized. In this study, the descriptive quantitative research method became a research method to describe how far students' understanding of the UNIMED FIK Sports Coaching Education Study Program is related to writing scientific articles that will be published in scientific journals. The population in this study were students of the FIK UNIMED Sports Coaching Education Study Program. The sample in this study were FIK UNIMED Sports Coaching Education students class of 2015 - 2022, namely 912 students who were actively studying. The conclusions from this study are: 1. Most of the Sports Coaching Education students, more than 50% of the students already know about scientific journal articles and get material related to scientific journal articles in lectures, but more than 50% of the respondents do not know the steps of writing the scientific journal. 2. More than 50% of respondents have never written scientific journal articles to be journalized and more than 50% of respondents who are interested in writing scientific journal articles, survey results of respondents stated through the survey that scientific journal articles are very important. 3. On average, Sports Coaching Education students never publish scientific journal articles and around 80% of students are also interested in further writing scientific journal articles that will be journalized to publish theses that students will make journals.Â